1994
DOI: 10.1016/s0006-3495(94)80929-4
|View full text |Cite
|
Sign up to set email alerts
|

Noise analysis of ion current through the open and the sugar-induced closed state of the LamB channel of Escherichia coli outer membrane: evaluation of the sugar binding kinetics to the channel interior

Abstract: LamB, a sugar-specific channel of Escherichia coli outer membrane was reconstituted into lipid bilayer membranes and the current noise was investigated using fast Fourier transformation. The current noise through the open channels had a rather small spectral density, which was a function of the inverse frequency up to about 100 Hz. The spectral density of the noise of the open LamB channels was a quadratic function of the applied voltage. Its magnitude was not correlated to the number of channels in the lipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
137
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(146 citation statements)
references
References 46 publications
8
137
1
Order By: Relevance
“…The frequency of closing events is sugar concentration dependent and is related to the k on rate of sugar binding, while the time the channel is in the closed state reflects the k off rate. The power spectrum of the time course of the ion current was fitted with a Lorentzian, yielding k on and k off rates (11,15). In symmetric-sugar conditions (sugar added to both compartments), these rate constants reflect access from and release to both sides of the channel.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of closing events is sugar concentration dependent and is related to the k on rate of sugar binding, while the time the channel is in the closed state reflects the k off rate. The power spectrum of the time course of the ion current was fitted with a Lorentzian, yielding k on and k off rates (11,15). In symmetric-sugar conditions (sugar added to both compartments), these rate constants reflect access from and release to both sides of the channel.…”
Section: Methodsmentioning
confidence: 99%
“…Association and dissociation rates were derived from sugar-induced current-noise analysis (2,15). The role of the residues of the polar tracks has been investigated in a separate study (8).…”
mentioning
confidence: 99%
“…Inspection of the porin structure suggests that the permeation of molecules through the channel is driven by molecular interactions with the surface rather than by free diffusion 68,69 . The first evidence for facilitated diffusion through a binding site was found in maltoporin, a maltose-specific channel from the outer membrane in E. coli [70][71][72][73] . a closer look at the OmpF structure revealed that it possesses a possible affinity site for ampicillin molecules (FIG.…”
Section: Physico-chemical Basis Of Porin Transportmentioning
confidence: 99%
“…The average through maltoporin (lamb) led to the development of an asymmetric single-binding-site model [70][71][72][73] The symbols P and aP indicate a channel state that is unoccupied or occupied by a bound antibiotic molecule, respectively; a and a′′ indicate free extracellular and periplasmic substrate, respectively.…”
Section: Box 3 | Electrophysiology Studiesmentioning
confidence: 99%
“…Derivation of the Individual Rate Constants of Sugar Binding-The binding of carbohydrates to the maltoporin channels was assumed for a long time to be symmetric (9,12), so that once a sugar molecule is bound inside the pore it would have equal probability to translocate or to exit to the same side. Only recent measurements performed on individual maltoporin trimers demonstrated that the association rate is 3-5-fold different depending on the sugar entrance side (18,19).…”
Section: For Details)mentioning
confidence: 99%